Adjuvant treatment with yupingfeng granules for recurrent respiratory tract infections in children: A systematic review and meta-analysis - Lu Zhang; Xuqiong Wang; Dong Wang; Yinling Guo; Xinying Zhou; Haiyan Yu (Frontiers Media S.A., 2022)
BackgroundYupingfeng granules (YPFG) contribute to various chronic respiratory infections. Several clinical studies have evaluated its efficacy and safety in treating recurrent respiratory tract infections (RRTIs) in children. However, the evidence for its use has not been conclusively proven.ObjectiveThe aim of this study was to demonstrate the efficacy and safety of YPFG in the adjuvant treatment of RRTIs in children.MethodsWe searched PubMed, Embase, Web of Science, Cochrane Library, Clinical Trials, Chinese Clinical Trial Registry, Sinomad, China National Knowledge Infrastructure (CNKI), Wanfang Database, and Chinese Scientific Journals Database (VIP) for randomized controlled trials (RCTs) of YPFG adjuvant therapy for children with RRTIs as of September 1, 2022. We screened the literature for inclusion and exclusion criteria, assessed the quality of each included literature, and then extracted data from each study for this systematic review and meta-analysis.ResultsA total of 17 RCTs were included. Data analysis showed that the total clinical response rate in the YPFG group was significantly higher than that in the control group [risk ratio (RR) = 1.18, 95%CI (1.12, 1.24), I2 = 39%, P < 0.00001]. Compared with the control group, three serum immunoglobulin levels were significantly increased in the YPFG group: IgA level [standardized mean difference (SMD) = 1.23, 95%CI (0.68, 1.78), I2 = 95%, P < 0.0001]; IgM level [SMD = 0.85, 95%CI (0.35, 1.35), I2 = 93%, P = 0.0009]; IgG level [SMD = 1.06, 95%CI (0.65, 1.47), I2 = 91%, P < 0.00001]. The TNF-α level was significantly lower in the YPFG group [SMD = −1.03, 95%CI (−1.55, −0.51), I2 = 84%, P = 0.0001] compared with the control group.ConclusionsIn summary, adjuvant YPFG therapy improves clinical efficacy and immunity in children with RRTIs. However, the effectiveness and safety of YPFG remain to be further verified.Systematic review registration[https://inplasy.com/inplasy-2022-3-0150/], identifier [INPLASY202230150].